Analysis of Influencing Factors High Turnover Rate of Nurses At RSU Anwar Medika Sidoarjo - Sri Wahyuni (Publikasi Indonesia, 2024)
This study aims to analyze the factors causing the high turnover of nurses at Anwar Medika Sidoarjo Hospital and compile steps to reduce the nurse turnover ratio at Anwar Medika Hospital. This research was conducted using a descriptive method where this research was carried out with the main aim of making an objective picture of a situation with hindsight. The nurse turnover ratio at RSU Anwar Medika Sidoarjo for December 2021-November 2022 was 25.2%. As much as 42% is involuntary turnover. Moreover, the remaining 58% is voluntary turnover. The voluntary turnover was further sorted, and 38 people were included in the controlled turnover. Most nurses leave RSU Anwar Medika Sidoarjo because they get jobs in other places considered more attractive, both in private companies and as civil servants. Then, the following most common reason relates to management policies in appointing permanent employees who are considered too long and policies regarding income.